2013
DOI: 10.2500/ajra.2013.27.3939
|View full text |Cite
|
Sign up to set email alerts
|

Objective Olfactory Outcomes after Revision Endoscopic Sinus Surgery

Abstract: RESS resulted in objective evidence of olfactory improvement in approximately one-half of our cohort over 16 months of follow-up and offers a treatment option for an otherwise poor prognosis condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 40 publications
2
50
1
2
Order By: Relevance
“…Of all the included studies, improvement in olfaction after sinus surgery was described in all 24 publications, except for one . However, this was true for only certain subgroups in nine studies . The main distinguishing factor for a positive outcome in these studies was the presence of polyps, revision versus primary surgery, or anosmia versus hyposmia preoperatively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of all the included studies, improvement in olfaction after sinus surgery was described in all 24 publications, except for one . However, this was true for only certain subgroups in nine studies . The main distinguishing factor for a positive outcome in these studies was the presence of polyps, revision versus primary surgery, or anosmia versus hyposmia preoperatively.…”
Section: Resultsmentioning
confidence: 99%
“…After close evaluation of the publications, 24 studies reached the inclusion criteria for this review. These have been published over the last 20 years and used the USPIT or single components or the whole battery of the Sniffin’ Sticks test . Almost all the included studies were published in the period from 2007 to 2018; only one earlier study from 1994 was identified …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The only significant prognostic factor that seems consistent across several studies is that patients with CRSwNP have a better chance for improvement in smell compared with those patients with CRSsNP. 12,36,37 Removing polyps alleviates obstruction, improves nasal airflow, and allows odorant molecules a better chance to reach the olfactory receptors.…”
Section: Impact Of Endoscopic Sinus Surgery On Olfaction In Chronic Rmentioning
confidence: 99%